TikTok Videos Enhance the Understanding of Food Processing among Grade 9 Technology Learners - Maphakane, Thabang; Ncisana, Lusanda; Nkosi, Praygod Bonginkosi (Research in Social Sciences and Technology- OpenED Network, 2025)
This study investigated the effectiveness of TikTok videos in enhancing Grade 9 Technology learners’ understanding of food processing. Grounded in constructivist theory, the research employed a mixed-method approach using a Concurrent Embedded Design. A total of 120 learners were sampled from three schools within the Lebowakgomo Circuit, Limpopo, South Africa. Quantitative data was collected through pre- and post-test scores, while qualitative data was collected through analysing the scripts of the learners. The findings revealed that learners who were taught using TikTok videos achieved higher scores than learners who received instruction through traditional lecture method. The findings further discovered that TikTok videos are effective in enhancing the understanding of subject matter. Our study results highlight the potential of digital platforms to enhance teaching, particularly in practical and conceptual subjects. This study recommends that teachers incorporate TikTok videos into their teaching methods to enhance conceptual understanding and make lessons more engaging. Teachers should consider creating TikTok accounts to share educational content, providing learners with accessible resources for self-study.